Training needs of mushroom (agaricus biosporus) farmers in Oyo state, Nigeria (2019)
The study examined the training needs of mushroom farmers and other factors hindering its production in Oyo State. Multi stage sampling procedure was used to select 143 mushroom farmers and data collected through interview schedule were analyzed using percentage, Chi-squared and correlation statistics at 0.05 probability level. Results showed that almost all (94.4%) were knowledgeable about mushroom production and 64.3% had high knowledge of mushroom benefits. Major constraint faced by the mushroom farmers was poor sales (72.7%). Trainings were needed in mixing/exposure period of substrate (42.9%), absolute infection free (91.4%), chemical preservation (88.8%), and quick freezing (71.8%). On the aggregate, the majority (63.6%) of the farmers have high training needs. There was a significant relationship between farmers’ educational level (x2=9.347), monthly income (x2=19.184), scale of production (x2=34.493), constraint (r=-0.452) and their training needs. A significant negative relationship was observed between knowledge (r= -0.362) of mushroom farmers, benefits derived (r= -0.200) and their training needs. Farmers require high level of trainings in mushroom production. Therefore, research institute and government should further intensify effort in sensitization and training of farmers on mushroom production so as to aid its increased production.